2019
DOI: 10.5539/jfr.v8n3p50
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing Methods on the Physicochemical, Mineral and Carotene Content of Orange Fleshed Sweet Potato (OFSP)

Abstract: The effect of processing methods on the physiochemical, mineral, vitamin C and carotenoid content of orange fleshed sweet potatoes were investigated. The processing methods used were boiling, steaming, roasting, frying and microwaving. The result of the proximate composition showed that the roasted orange fleshed sweet potatoes (OFSP) had the highest ash content ranging from 0.32-0.99%, crude protein 0.96-3.12%, crude fiber 0.50-3.40% and carbohydrate content 13.98-40.10% with a decrease in the moisture conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The present data is comparable with 22 who reported that white variety of Jerusalem artichoke tuber had 300.12 ± 30.01 mg/100 g potassium content. Likewise, the potassium content of boiled sweet potato (3,061.08 mg/100 g) was significantly reduced when compared with unprocessed (3,288.24 mg/100 g) 29 . The reduction of potassium content may be the result of leaching of its content during processing.…”
Section: Resultsmentioning
confidence: 96%
“…The present data is comparable with 22 who reported that white variety of Jerusalem artichoke tuber had 300.12 ± 30.01 mg/100 g potassium content. Likewise, the potassium content of boiled sweet potato (3,061.08 mg/100 g) was significantly reduced when compared with unprocessed (3,288.24 mg/100 g) 29 . The reduction of potassium content may be the result of leaching of its content during processing.…”
Section: Resultsmentioning
confidence: 96%
“…Tis could be explained by the low iron and zinc content of mashed sweet potato compared to the unfortifed pearl millet gruel. A comparison of results obtained by Hurrell and Egli [49], Mohanraj and Sivasankar [38], and Eke-Ejiofor and Onyeso [48] revealed the superiority of pear millet grains on sweet potato tubers as far as iron and zinc contents are concerned. Te incorporation of mashed sweet potato into the control consequently reduced the iron and zinc contents of fortifed gruels.…”
Section: Mineral Contents Of Mashed Sweet Potato and Fortifedmentioning
confidence: 84%
“…Tis may be due to the diluting efect of added mashed sweet potato, which had low ash content compared to the unfortifed gruel. Previous studies revealed relatively poor mineral content of sweet potato tubers [42,47,48]. Also, leaching of minerals through difusion in boiling water would have occurred during the cooking step of the preparation of mashed sweet potato.…”
Section: Mineral Contents Of Mashed Sweet Potato and Fortifedmentioning
confidence: 99%
“…The physicochemical properties of foods are noticeably changed during the roasting process. Many published works have investigated the effect of roasting conditions on the properties of several products (Eke-Ejiofor & Onyeso, 2019;Rabiou et al, 2018b;Marzocchi, 2017). The results of the proximate composition showed that the moisture content of Gabou was lower than that of various dried vegetative parts of the onion and the minimum recommended moisture content of 4% for dried onion (Rozis and Guinebault, 1995).…”
Section: Discussionmentioning
confidence: 99%